Identification and test of active protein resemble Ribosomr-inactivating proteins (RIPs) on Kaemferia rotunda Linn - Wiryatun Lestariana Wiryatun Lestariana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Statistically data of US Mortality showed that percentage cause of the death of the cancer is in second place after the heart diseases. Indonesia, Java especially Daerah Istimewa Yogyakarta, the data of The Dr. Sardjito hospital showed that the patients of cancer was increasing in the last year. Indonesian, especially Javanese, uses white turmeric to prevent and to treat cancer. There are some varieties of turmeric available commercially such as Curcuma (Cl mangga Val & Jijp, C. zeodaria and Kaemferia (K) rotunda Linn. The studies showed that C. mangga contain proteins compound that resembles Ribosome-inactivating proteins (RIPs) which have activity to cleave supercoiled DNA. In vitro study indicated that the addition of crude extract of C. mangga on cancer cell-lines (B-LCL, EBV cells and Raji cell-lines) and normal lymphocytes, the percentage of cytotoxic effect on those cancer cell-lines were higher significantly than normal cells.Objective: The aim of the study was to know the presence of RIPs activity in K. rotunda Linn by the ability of the RIPs in cleaving the supercoiled DNA.Methods: The rhizomes of K. rotunda Linn that was in part dried at 40Â°C. Both wet and dried rhizomes are pounded and then extracted. The resulting crude extract was precipitated to obtain its protein fraction. The crude extract and protein with various concentrations were incubated with the supercoiled DNA and agarose gel electrophoresis was used to test its activity in cleaving the supercoiled DNA. The activity test was done by observing 3 criterions, viz. the thinning of the supercoiled DNA, the circular band thickening and the appearance of the linear band which were subsequently compared to the plasmid DNA without treatment.Result: The results showed that both crude extracts and proteins of both wet and dried samples were able to cleave supercoiled DNA into circular and linear form. The increasing concentrations of the crude extract and the protein resulted in increasing the activity which was indicated by the thickening of circular band and the appearance of the linear band .Conclusion: Kaemferia rotunda contains proteins compound that resemble Ribosome-inactivating proteins (RIPs).which have ability to cleave supercoiled DNA to be circular and linear DNA.Key words: ribosome-inactivating proteins (RIPs) - supercoiled DNA - circular DNA - linear DNA - Kaemferia rotunda Linn